Effectiveness of Using the Hypnosleep Method in Shaping Children's Character Based on Ibn Kathir's Interpretation of Quran Surah Al-Baqarah Verses 285-286 - Siti Munawati; Aslihatul Rahmawati (Unram Journal of Community Service, 2025)
This Community Service Program aims to enhance the role of parents in shaping their children's character through the application of the Hypnosleep method, inspired by Ibn Kathir's interpretation of verses 285-286 of Surah Al-Baqarah. Current issues in character building show a gap between theoretical religious understanding and the internalization of moral and spiritual values in daily actions. As a solution, Hypnosleep is introduced, a subconscious suggestion technique applied when children are in a light sleep state, when the mind is more receptive to positive suggestions. This program was carried out using the Participatory Action Research (PAR) approach, involving mothers from the Nurul Amin Religious Study Group in Tangerang, Indonesia, as active participants in every process of planning, implementation, and evaluation. The training provided theoretical insights and practical guidance on how to incorporate Qur'anic values—such as faith, responsibility, belief in God, and Divine love—into Hypnosleep practices based on the understanding of Ibn Kathir. Evaluation showed a high level of participant engagement and satisfaction, as well as an improvement in parents' understanding, skills, and self-confidence in utilizing positive subconscious communication to support their children's character development. These results indicate that Hypnosleep has the potential to be an effective, gentle, and spiritually aligned strategy for instilling Islamic character, as long as it is applied ethically and sustainably within a supportive family environment. The program highlights the potential for collaboration between Islamic spirituality and educational psychology, offering a comprehensive framework for character education that complements formal education. Moving forward, this approach is expected to contribute to the development of young generations with strong Qur'anic character, emotional stability, and moral integrity.